A most improbable story - Theroux, Steven J., author.
1 online resource
Keywords: "This book is a "big history" of the evidence regarding how we came to be. It explores philosophical thought and how our past might affect our future. The text reviews different perspectives and the strengths and weaknesses of each. This journey highlights the history of life, the emergence of life forms, and the evolution of complex creatures"--